Intertemporal labor supply and involuntary unemployment - Peter Haan; Arne Uhlendorff (Institute for the Study of Labor (IZA), 2007)
In this paper we develop a model to consistently estimate the intertemporal labor supply behavior on the extensive margin (participation decision) and the intensive margin (working hours decision). In this framework we distinguish between voluntary non-participation and involuntary unemployment which is caused by labor market rationing and model the dynamics of labor supply by accounting for true state dependence and unobserved effects. Our approach follows the empirical literature on life cycle employment based on approximate decision rules. However, in contrast to previous studies, this framework allows us to test for true state dependence of voluntary non-participation, involuntary unemployment, full-time work and over-time work. Moreover, we derive consistent estimates of intertemporal labor supply elasticities over time and asses the bias of short- and long-run elasticities derived in a pure choice model of labor supply.
Keywords: 330; Arbeitsangebot; Zeitpräferenz; Unfreiwillige Arbeitslosigkeit; Arbeitslosigkeit; Deutschland